Reflection methods: Tools to make learning more meaningful - Gordijn, Femke; Eernstman, Natalia; Helder, Jan; Brouwer, Herman (Wageningen Centre for Development Innovation, 2018)
This handbook summarises methods that can be used to facilitate the pr ocess of reflection on the knowledge and experiences people acquire du ring a capacity development trajectory or training event. We believe t hat by explicitly integrating reflection in the learning process the l earning will become clearer and better articulated and will contribute more strongly to meaningful change. Therefore we advise facilitators to deliberately include reflective learning sessions in their process design and implementation. This handbook can inspire you to do so and provides many methods which help to facilitate this.